Ansiedad y su influencia en el rendimiento académico de una adolescente de 16 años del cantón San Miguel - Mora Velasco, Maria Gabriela (2021)
In this paper, it will be exposed the case of a teennager who presents anxiety symptoms and whether this emotion is influencing on her academic performance. It contains the research line of the career "Prevention and Diagnosis", and its sub-line of research " Behavioral disorders and their impact on the teaching-learning process”.The case study was carried out with a qualitative methodological approach, which was of main importance to start from the general to the particular, in order to get a better understanding of the problem to be worked on, as well as the psychological approach from the cognitive-behavioral approach. It is worth mentioning that it presents an exploratory research scope that will be highlighted within the development of the case study, which includes its due justification, theoretical support, applied techniques, results obtained and conclusion. Anxiety normally manifests when the person is in a state of real threat, however, it is not normal when it is present when only the mind creates that threat without any external stimulus. From the CBT (Cognitive Behavioral Therapy) psychological approach, this emotion is caused by the presence of automatic thoughts. Academic performance is the way in which the student responds to the tasks assigned within the educational field. The direct beneficiary will be the university community of psychologists, since the case study proposes a tentative therapeutic scheme for intervention in anxiety disorders. There were applied four hours of psychological interviews in total, where the respective diagnosis was made: Generalized Anxiety Disorder with code F41. In order to continue with psychotherapeutic treatment.